APPAREL BRAND ENDORSERS AND THEIR EFFECTS ON PURCHASE INTENTIONS: A STUDY OF PHILIPPINE CONSUMERS - Rodriguez, Karina P. (Philippine Management Review; Vol 15 (2008), 2009)
This study explores the effects of endorser type (celebrity and anonymous) and endorser credibility on consumers’ attitudes and purchase intentions. It also explores the moderating effect of culture on the influences of spokesperson type and spokesperson credibility on attitude towards the advertisement of Filipino consumers. The research data indicate that the higher the celebrity status of the endorsers featured in an advertisement, the higher the purchase intentions of consumers. For spokesperson credibility, the only characteristics which have a significant influence on intentions to purchase are: Experienced, Knowledgeable, Qualified, and Trustworthy. In addition, power distance and collectivism seem to have a substantial moderating effect on the relationship between spokesperson type and credibility, and attitude towards the advertisement.
Keywords: celebrity endorser, credible endorser, collectivism, and power distance